Making Public Places Safer: Surveillance and Crime Prevention - Welsh, Brandon (Studies in Crime and Public Policy Ser., 2009)
Making Public Places Safer is the first book to assess the effectiveness and social costs of the most important surveillance methods to prevent crime in public space: CCTV, improved street lighting, security guards, place managers, and defensible space. Importantly, the book goes beyond the question of "Does it work?" and examines the specific conditions and contexts under which these surveillance methods may have an effect on crime as well as the mechanisms that bring about a reduction in crime. Making Public Places Safer is a timely and reliable guide at a time when cities need cost-effective methods to fight crime and the public gradually awakens to the burdens of sacrificing their privacy and civil rights for security.